The velocity extraction and feature analysis of glacier surface motion in the Gongar region based on multi-source remote sensing data - Gu, Fang; Zhang, Sicong; Zhang, Qinqin; Li, Dan; Fu, Yingzi; Chen, Xuehua (Frontiers in Earth Science, 2024)
The movement of glaciers plays a crucial role in environmental and geological processes, significantly influencing the formation and dynamics of ice bodies. Currently, remote sensing data is used to obtain glacier movement characteristics. However, different remote sensing data sources lead to variations in the extracted glacier features. Therefore, identifying a reliable data source and method is of great significance. This study leverages feature tracking technology to analyze optical and Synthetic Aperture Radar (SAR) remote sensing imagery, specifically GF-1 optical images and GF-3, Sentinel-1 SAR images, captured during the 2020 to 2021 ablation season in Gongar. The aim was to quantify glacier surface velocities and to evaluate the comparative effectiveness of different remote sensing modalities in capturing these dynamics. Our findings indicate a strong consistency in the spatial distribution of glacier surface velocities derived from diverse remote sensing data sources, with high-precision optical imagery (GF-1) yielding the most accurate velocity measurements, followed by Sentinel-1 SAR data. Notably, large glaciers in Gongar exhibited rapid movements, with an average velocity of 0.16 m/d, primarily at elevations between 4500 and 6500 meters. The fastest velocities were recorded at approximately 4500 meters elevation. Glaciers with inclines ranging from 10° to 60° displayed the highest velocities within the 20° to 30° slope range. It was observed that glaciers on the southeast slope moved faster, exhibiting the highest average surface velocity, in contrast to those on the west slope, which moved more slowly. The study also reveals that the effectiveness of different remote sensing data in detecting glacier velocity in Gongar, with high-resolution data more accurately capturing surface velocities in melting areas or those with slower movement. This study underscores the importance of multisource remote sensing data in understanding glacier dynamics and contributes valuable insights into the mechanisms driving glacier movements.